2022
DOI: 10.1111/jdi.13805
|View full text |Cite
|
Sign up to set email alerts
|

Transition of cardiometabolic status and the risk of type 2 diabetes mellitus among middle‐aged and older Chinese: A national cohort study

Abstract: Aims/Introduction: The cardiometabolic index (CMI) has been proposed as a novel indicator of cardiometabolic status. This study aimed to investigate the effects of CMI and its longitudinal transitions on the development of type 2 diabetes mellitus in middle-aged and older Chinese. Materials and Methods: We used data from the China Health and Retirement Longitudinal Study (2011-2018). CMI was calculated as the product of the waist circumference to height ratio and the triglyceride to high-density lipoprotein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(56 reference statements)
2
5
0
Order By: Relevance
“…Specifically, stronger relationships were observed in the CMIQ4 groups. Notably, there were gender disparities that females were found to have a higher risk of IR, IFG, and T2DM than males in our study, and it appears to have been found consistent with several prior studies in Chinese and Japanese populations ( 21 , 22 ). Sex distributions could be related to various mechanisms, including fat micro-environment, cell-intrinsic characteristics, and sex hormones ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, stronger relationships were observed in the CMIQ4 groups. Notably, there were gender disparities that females were found to have a higher risk of IR, IFG, and T2DM than males in our study, and it appears to have been found consistent with several prior studies in Chinese and Japanese populations ( 21 , 22 ). Sex distributions could be related to various mechanisms, including fat micro-environment, cell-intrinsic characteristics, and sex hormones ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in Chinese and Japanese populations have demonstrated that CMI is a predictor of diabetes ( 21 , 22 ). However, sparse comprehensive studies are available to ascertain the capability of CMI in identifying individuals with IR and T2DM, especially with IFG, in US adults.…”
Section: Introductionmentioning
confidence: 98%
“…( 11 ) discovered that after adjusting for age and histories of regular exercise, alcohol drinking, and smoking, there was a stronger association between CMI and diabetes. A longitudinal study of 7347 middle-aged and elderly Chinese showed that individuals with high CMI had a far higher risk of developing type 2 diabetes after adjusting for region, sex, age, marital status, ln(per capita expenditures), education, hypertension, drinking, smoking, low-density lipoprotein cholesterol (LDL-C), and TC ( 13 ). This study involved 15453 Japanese adults, and we found that the incidence of diabetes was higher with increased CMI levels.…”
Section: Discussionmentioning
confidence: 99%
“…An increased CMI poses a risk for individuals with T2DM and is recognized as a detrimental factor. To effectively prevent the onset of T2DM, appropriate measures should be implemented to mitigate the escalation of the CMI from low to high values [ 15 , 16 ]. Additionally, the CMI exhibited positive correlations with diastolic blood pressure, systolic blood pressure, BMI, hip circumference, glucose (at 0 min), insulin (at 0 min), insulin (at 120 min), HOMA-IR, TC and PWV values.…”
Section: Discussionmentioning
confidence: 99%